Influence of reprocessing on fibre length distribution, tensile strength and impact strength of injection moulded cellulose fibre-reinforced polylactide (PLA) composites - N. Graupner; K. Albrecht; G. Ziegmann; H. Enzler; J. Muessig (eXPRESS Polymer Letters)
The present study focuses on the reprocessing behaviour of recycled injection moulded polylactide (PLA) composites. The composites are reinforced with regenerated cellulose fibres (lyocell) of variable fineness and a fibre mass content of 30%. They were reprocessed up to three times. The influence of reprocessing on the fibre length distribution and the resulting composite mechanical properties (tensile and impact strength) was analysed. While the first reprocessing cycle does not affect the mechanical characteristics of the neat PLA matrix, the strength of the composites decreases significantly due to a decreasing fibre aspect ratio. It was shown that fibres having a larger cross-sectional area display a lower aspect ratio than finer fibres, after reprocessing. This phenomenon leads to a larger decrease in tensile strength of composites reinforced with coarser fibres when compared to composites reinforced with finer fibres. A comparison of virgin composites and threefold reprocessed composites with a similar fibre length distribution resulted in a significantly higher tensile strength compared to the virgin sample. This result leads to the conclusion that not only the fibre length is drastically reduced by reprocessing but also that the fibres and the matrix were damaged.